Plasma level of D-dimer accompanying different types of gynecologic surgery and effects of prophylactic subcutaneous injection of heparin calcium - Yanai, Sakika; Nakano, Yusuke; Honda, Ken-ichi; Sumikura, Tomoko; Seo, Saori; Inoue, Yutaka; Umesaki, Naohiko (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The standard range of D-dimer level associated with each type of gynecologic surgery is required to note the occurrence of bleeding or thromboembolism. Methods: Plasma levels of D-dimer of patients who underwent different types of gynecologic surgery were measured on the Day of Preoperative Examination (DPE) and the first postoperative day (POD-1). Patients were classified by surgery type: hysterectomy for benign diseases or cervical intraepithelial neoplasia; hysterectomy for uterine cancer; surgery for ovarian cancer; laparoscopic surgery for a benign adnexal mass; laparotomy for a benign adnexal mass; laparotomic myomectomy; cervical conization; transcervical resection of an intrauterine mass; vaginal surgery for prolapse of a pelvic organ. Results: In each type of gynecologic surgery, plasma levels of D-dimer on POD-1 were higher than those on the DPE. Prophylactic subcutaneous injection of heparin calcium for patients who underwent surgery for endometrial cancer showed no significant difference in the plasma level of D-dimer on the sixth postoperative day (POD-6) and the plasma level of D-dimer on POD-6 was in the same level as those on POD-1. Conclusions: Plasma levels of D-dimer on POD-1 were higher than those on the DPE in each type of gynecologic surgery. The D-dimer level remained high even on POD-6, and not changed by prophylactic subcutaneous injection of heparin calcium.